National Pediatric Dermatology Nosologic Statistics Analysis 2009-2013. Pediatric Dermatology Portuguese Group - Osório Ferreira, Eduarda (2016)
The Pediatric Dermatology Portuguese Group performed a survey of the national nosologic statistic of the years 2009- 2013, collecting data from 12 national hospitals with a consultation of pediatric dermatology. A total of 22,354 patients were studied. Eczemas were the most common diseases, with 5,104 patients (22.3%), followed by nevi - 4,678 (20.4%), infections - 4,651 (20.3%), adnexal diseases - 2,770 (12.1%), vascular diseases - 1,066 (4.7%) and pigmentary disorders - 1,033 (4.5%). Furthermore, a comparative analysis was performed with nosologic statistics from ten years ago. In our opinion these studies are important since they allow us to know the national prevalence of pediatric cutaneous diseases, their evolution and aid us in establishing comparison with studies from other countries. Finally, they may help to improve preventive medicine.